"Stalked by the state": GPS surveillance technology and sex offender parolees = "Stalked by the state" : GPS-Überwachungstechnologien und Sexualstraftäter auf Bewährung - Troshynski, Emily I. (Kriminologisches Journal, 2017)
Based on feminist Science and Technology Studies (STS) frameworks that conceive of technology as both a source and consequence of gendered relations, this paper explores a criminological topic of concern: Global Positioning Systems (GPS) as a tool for the management of sex offender parolees in the community. Previous criminological research on this topic has largely focused on experimental/quantitative projects dedicated to understanding the effectiveness of GPS surveillance technology to curb re-offending patterns. Instead, this paper focuses on narratives with sex offenders in the USA as they articulate their understandings of GPS including their everyday experiences with a technology that tracks and monitors them for life. Therefore, qualitative research with sex offender parolees living with GPS will highlight themes associated with adverse feelings, body modifications, and responsiblisation techniques. Specifically, Donna Haraway´s (1991) cyborg will be used as a metaphor for analysing the sociotechnical relationships to whichthese participants find themselves involved.